Exploring the factors affecting the gap on literacy skills among students with learning disabilities: a case study - Mohamed Zaki, Nur Farhana; Ahmad, Nor Aniza; Mohamed 'Ashri, Muhammad 'Ilman (Human Resource Management Academic Research Society, 2019)
The wide gap in literacy proficiency among students with learning disabilities is one of the rising issues in education field. This study is conducted to find out the factors that contribute towards the gap on literacy skills among students with learning disabilities and mainstream students. Furthermore, teachers’ strategy to improve the literacy skills among learning disabilities students also inquired. Besides, this study also discussed about the interventions or programs that have been implemented to help these students. An interview with three special needs teachers at Sekolah Kebangsaan Putrajaya Presint 16(2) is conducted to investigate this issue. The findings shows that lack of awareness among parents which then causing their children to received late interventions is among the causes for unsatisfactory literacy skills. It is important for teachers to use variety of teaching strategies to reduce the gap on literacy skills. At the end of this paper, the author discussed on how to enhance the intervention programs and what teachers and parents role to fit the needs of these students. The findings of this study provide new dimension in explaining the importance in reducing the gap on literacy skills among special education needs students.